PENGARUH DUKUNGAN SOSIAL DAN SELF EFFICACY TERHADAP PERILAKU AKTIVITAS FISIK MAHASISWA - Septian, Adly; Subarjah, Herman; Zaky, Mohammad (Fakultas Ilmu Keolahragaan Unimed, 2024)
This research aims to determine the influence of social support and self-efficacy on students' physical activity behavior. The design used in this research is correlational with random sampling techniques. The total sample from this research was 70 respondents from sports science students in 2022. The instruments used in this research were the Social Support Exercise Survey questionnaire, the Exercise Self-Efficacy Scale, and the International Physical Activity Questionnaire. After that, the results of the research data were analyzed using multiple linear analysis parametric tests with the IBM SPSS version 25 application because the data was normally distributed. The results of the analysis show that there is family influence on students' physical activity with a value of Sig. < 0.05 and t value > 1.998, for the influence of friend support there is no influence on students' physical activity with a value of Sig. > 0.05 and the calculated t value < 1.998, for the influence of self-efficacy there is an influence on students' physical activity with a Sig value. < 0.05 and tcount > 1.998.